Effects of community-based intervention of non-government organization on gender equity in agriculture and food systems in selected areas of Kishoreganj district - Lecoutere, Els; Puskur, Ranjitha; Singaraju, Niyati; Mishra, Avni; Akhter, Sadika; Khatun, Fatema; Rahman, Aminur; Kamruzzaman, Mohammed; Chowdhury, Promit Barua (2023)
This impact assessment study focuses on two community-based development projects, implemented by People's Oriented Programme Implementation (POPI), an NGO in Bangladesh. Both projects were implemented in the Kishoreganj district, a gender inequality hotspot. The "Engaging Communities and Authority to Tackle Oppressions (ECATTO)" project focused on agriculture and livelihoods promotions to ensure increased equitable access to income for both women and men, nutritious food for men, women, boys, and girls, and promoting women's empowerment and gender equity at the family and community level. The "Strengthening Household Ability to Respond to Development Opportunities (SHOUHARDO)–III," project aimed at sustainably reducing food insecurity of the poor and extremely poor households in the project areas. The impact study considered key domains in transforming food systems to explore the hypothesized relationships between the changes intended through our pilot intervention and the envisioned gender equality outcomes.